PDTM-32. RESOLVING MEDULLOBLASTOMA CELLULAR ARCHITECTURE BY SINGLE-CELL GENOMICS. (11th November 2019) - Bihannic, Laure; Hovestadt, Volker; Smith, Kyle; Filbin, Mariella; Shaw, McKenzie; Baumgartner, Alicia; DeWitt, John; Groves, Andrew; Mayr, Lisa; Weisman, Hannah; Richman, Alyssa; Shore, Marni; et al.
Abstract: Medulloblastoma is a malignant childhood cerebellar tumor comprised of distinct molecular subgroups. Whereas genomic characteristics of these subgroups are well defined, the extent to which cellular diversity underlies their divergent biology and clinical behaviour remains largely unexplored. We used single-cell transcriptomics to investigate intra- and inter-tumoral heterogeneity in twenty-five medulloblastomas spanning all molecular subgroups. WNT, SHH, and Group 3 tumors comprised subgroup-specific undifferentiated and differentiated neuronal-like malignant populations, whereas Group 4 tumors were exclusively comprised of differentiated neuronal-like neoplastic cells. SHH tumors closely resembled granule neurons of varying differentiation states that correlated with patient age. Group 3 and Group 4 tumors exhibited a developmental trajectory from primitive progenitor-like to more mature neuronal-like cells, whose relative proportions distinguished these subgroups. Cross-species transcriptomics defined distinct glutamatergic populations as putative cells-of-origin for SHH and Group 4 subtypes. Collectively, these data provide novel insights into the cellular and developmental states underlying subtype-specific medulloblastoma biology.